Need Assessment of Colaboration between the Higher Education and the School based on Management Information System - Nurhattati Fuad; Suryadi Suryadi; Fadhillah Fadhillah; Fransiskus Sawan (Journal of International Conference Proceedings (JICP), 2019)
This study aims to analyze the needs of schools and higher education to collaborate in education by a management information system approach. This study used a qualitative approach. The method used is a mix method, through the stages of initial data collection and needs assessment and interview to the Principal of Elementary School and to Lecturers from Universitas Serambi Mekkah. The results of the study show that collaboration information management systems in education still use conventional information and technology, and are needed to expand information access needs between the two parties. Nevertheless, the readiness of some human resources to use technology still needs to be improved, the lack of supporting facilities is still an obstacle.